An Investigation on Development and Evaluation of Kanamycin Hydrogels for Wound Healing - Chaurasiya , Chanchal; Verma , Kajol; Tomar , Pooja; Verma , Rahul Kumar (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
The goal of this study is to create and test kanamycin for wound healing. Kanamycin is an antibiotic used as a first-line treatment. Kanamycin's absorption from the parentral pathway is improved by hydrogel. For the goal of wound healing, hydrogel outperforms traditional dose forms in terms of patient compliance. Carbomer (Carbopol) is utilized in the hydrogel formation. To improve the combining of the medication and the physical qualities of the hydrogel, five batches of hydrogel were made using varying concentrations of hydroxy propyl methyl cellulose and ethyl cellulose. The kanamycin is insoluble in PEG-400, but as per the procedure it is must to dissolve kanamycin in PEG-400. Therefore, a co-solvent study performed. Evaluation parameter such as appearance, solubility study, swelling measurement, spreadibility, percent drug entrapment efficiency, ph detection, and in-vitro release study were performed for hydrogels of each batch and batch- 3 was optimized best batch from all five batches. Batch-3 shows best solubility, swelling and percent drug entrapment properties. Batch-3 is able to release 91% drug release in 8 hr. The produced hydrogel shown good evaluation properties as well as storage stability. The hydrogel might be used as a medication delivery dosage form for a variety of reasons.